SILVER NANOPARTICLES CAPPED L-Cysteine AS A MERCURY ION DETECTOR BY COLORIMETRY: A JOURNAL REVIEW - Arrasyid, Rizky; Arif, Syaiful; Alimuddin, Alimuddin (PROSIDING SEMINAR KIMIA, 2023)
Nanoparticles are a field of research on the atomic scale with a particle size of 1-100 nm. There are many applications of nanoparticles in various fields, such as heavy metal detectors. One type of nanoparticle that can be used as a detector is L-Cysteine modified silver nanoparticles (AgNPs-L-Cys). Thus, the purpose of this review is to determine the ability of L-Cysteine modified silver nanoparticles to detect heavy metals from literature data. Based on the results of the literature, one of the heavy metals that can be detected using AgNPs-L-Cys is Hg. The color of the solution synthesized by AgNPs-L-Cys is a yellow solution. From the results of some literature, there are differences in color changes in the addition of Hg solution to AgNPs-L-Cys solutions such as changes in color from yellow to white, dark yellow to clear, and brown to light yellow. The maximum wavelengths for detecting Hg2+ metal ions from several literatures were found to be 420 nm, 410 nm, 392 nm and 390 nm. The linearity results were obtained in the range of 1-2500 nM with a relation coefficient of 0.994 and 40-1040 nM with a relation coefficient of 0.998. When compared to gold nanoparticles modified L-Cysteine (GNPs-Cys), AgNPs-L-Cys has a wider range where GNPs-Cys has a range of 100-2000 nM with a correlation coefficient of 0.9747. The LOD results obtained from several literatures were 45.39 nM and 8 nM. The % recovery results obtained from several literatures are 98.38% ± 14.1% and 91.5%∼109.1%. From these data, AgNPs-L-Cys can be used for the detection of Hg2+ metal ions with high selectivity, sensitivity, simplicity and detection speed. Keywords: Silver Nanoparticles, L-Cysteine, Mercury, Colorimetry